Blood Cells Counting Using Modified Circular Hough Transform - Madihah Mazalan, Siti; Huda Yusof, Khairul; Rashidah Ahmad Rashidi, Nur; Humaimi Mahmood, Nasrul; Azhar Abdul Razak, Mohd (International Journal of Engineering and Technology, 2026)
The number, size and shape of blood cells are used to diagnose the various types of diseases such as leukemia, dengue, malaria and etc. Manual cell counting is a traditional method to count the number of cells and to acknowledge the state of a person’s health conditions based on the blood content. Problems using the manual cell counting under the microscope are time consuming and able to give errors. Therefore, we proposed a method to detect and determine the total number of blood cells by using Modified Hough transform (MHT) method. The blood cells image is analyzed using the developed algorithm in MatLab. In image processing, the process involves preprocessing and segmentation to find the radius range of cells. Then, MHT method is used to determine the number of blood cells based on the radius range of cells. Sixty samples of human blood cell image were tested and the accuracy is 94%